2019
DOI: 10.1002/hep.30861
|View full text |Cite
|
Sign up to set email alerts
|

A Metallomic Approach to Assess Associations of Serum Metal Levels With Gallstones and Gallbladder Cancer

Abstract: Background and Aims Exposure to metals may promote the risk for cancers. We evaluated the associations of a broad spectrum of metals with gallbladder cancer (GBC) and gallstones. Approach and Results A total of 259 patients with GBC, 701 patients with gallstones, and 851 population‐based controls were enrolled in Shanghai, China. A metallome panel was used to simultaneously detect 18 metals in serum through inductively coupled plasma–mass spectrometry. Logistic regression models were used to estimate crude or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…Recent research has further proven that oral magnesium supplementation (800 mg magnesium oxide daily) prevents the postoperative complications of cardiac surgery, including nausea, vomiting and constipation in patients from the admission to discharge from hospital ( Moradian et al, 2017 ). The data from a clinical trial including a total of 259 patients with gallbladder cancer, 701 patients with gallstones, and 851 population-based controls in Shanghai, China, have demonstrated that serum magnesium level is inversely related to gallbladder disease ( Lee et al, 2020 ). Aquamin is a natural product rich in magnesium and calcium.…”
Section: Therapeutic Application Of Magnesium In Other Diseasesmentioning
confidence: 99%
“…Recent research has further proven that oral magnesium supplementation (800 mg magnesium oxide daily) prevents the postoperative complications of cardiac surgery, including nausea, vomiting and constipation in patients from the admission to discharge from hospital ( Moradian et al, 2017 ). The data from a clinical trial including a total of 259 patients with gallbladder cancer, 701 patients with gallstones, and 851 population-based controls in Shanghai, China, have demonstrated that serum magnesium level is inversely related to gallbladder disease ( Lee et al, 2020 ). Aquamin is a natural product rich in magnesium and calcium.…”
Section: Therapeutic Application Of Magnesium In Other Diseasesmentioning
confidence: 99%
“…Despite recent progress regarding the diagnosis and prognosis of gallbladder cancer (GBC), ( 24‐26 ) the lack of effective diagnostic biomarkers and intrinsic chemoresistance to first‐line drugs results in an extremely poor prognosis of GBC patients. ( 27‐31 ) Therefore, continued efforts are required for identification of reliable tumor markers that will facilitate the early detection of GBC, as well as effective cellular targets that might provide the basis for therapeutic approaches.…”
mentioning
confidence: 99%
“…It is assumed that people working in industries and their families living in the surrounding areas are more exposed to pollutants produced by the factories, and these may cause higher incidence of gallstones and other diseases in them. 5 With an aim to find out whether this assumption holds true in case of gallstone diseases and whether any other causal factor is identifiable in these patients, this study was undertaken.…”
Section: Resultsmentioning
confidence: 99%